Critical Analysis of Sadness in “To Helen” by Edgar Allan Poe (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study analyzes the representation of sadness in To Helen by Edgar Allan Poe. Although the poem is commonly interpreted as a celebration of beauty and classical ideals, this research argues that it also contains subtle expressions of emotional suffering, longing, and psychological alienation. The study aims to identify how sadness is constructed through imagery, symbolism, diction, tone, and idealization within the poem. This research employs a qualitative descriptive method using textual and interpretative analysis supported by psychological and biographical approaches. The primary data source is the poem itself, while secondary data are obtained from books, journal articles, and literary criticism related to Poe’s poetry and Dark Romanticism. The findings reveal that sadness in “To Helen” is expressed indirectly through emotional longing, escapism, nostalgia, and the idealization of beauty. The speaker’s emotional exhaustion and desire for refuge are reflected in classical imagery and symbolic language that portray Helen as an unattainable figure of comfort and perfection. Furthermore, the poem reflects characteristics of Dark Romanticism, particularly psychological conflict and emotional isolation. The study concludes that sadness in “To Helen” functions not only as an emotional theme but also as an aesthetic experience in which emotional pain is transformed into poetic beauty. Therefore, the poem demonstrates Poe’s ability to combine melancholy and artistic elegance through subtle and symbolic expression.
Keywords: Sadness; Dark Romanticism; idealization; emotional longing; Edgar Allan Poe